CD169+ classical monocyte as an important participant in Graves’ ophthalmopathy through CXCL12-CXCR4 axis - Dongliang Wang; Jie Ling; RongQiang Tan; Huishi Wang; Yixin Qu; Xingyi Li; Jinshan Lin; Qikai Zhang; Qiuling Hu; Zhong Liu; Zhaojing Lu; Yuheng Lin; et al. (iScience, 2024)
Summary: Patients with Graves’ disease (GD) can develop Graves’ ophthalmopathy (GO), but the underlying pathological mechanisms driving this development remain unclear. In our study, which included patients with GD and GO, we utilized single-cell RNA sequencing (scRNA-seq) and multiplatform analyses to investigate CD169+ classical monocytes, which secrete proinflammatory cytokines and are expanded through activated interferon signaling. We found that CD169+ clas_mono was clinically significant in predicting GO progression and prognosis, and differentiated into CD169+ macrophages that promote inflammation, adipogenesis, and fibrosis. Our murine model of early-stage GO showed that CD169+ classical monocytes accumulated in orbital tissue via the Cxcl12-Cxcr4 axis. Further studies are needed to investigate whether targeting circulating monocytes and the Cxcl12-Cxcr4 axis could alleviate GO progression.